Experimental toxicology : (Royal Society of Chemistry, 1993)
This volume addresses the basic issues concerned with the practice of experimental toxicology and discusses such issues as experimental design, biochemical issues, animal husbandry, species differentiation, carcinogenesis and laboratory design. It has been revised and updated to give special attention to recent advances in the areas of molecular, genetic and reproductive toxicology and in the knowledge regarding the multiplicity of enzymes involved in foreign compound metabolism.